PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENUMPANG DI TERMINAL RAJEKWESI BOJONEGORO - Endang Endang; Laily Nur Cholidah (Jurnal Teknika, 2017)
This study aims to determine the effect of simultaneous variables X1 (facilities) and X2 (service quality) to variable Y (satisfaction) and know the partial influence of variable X1 (facility) and X2 (service quality) to variable Y (satisfaction). Sampling technique using accidental sampling. Data collection method in this research is using primary data and secondary data. Data were analyzed by using multiple linear regression with the help of SPSS 23. Based on the result of t test data analysis variable X1 (facility) and X2 (service quality) partially have no significant effect on passenger satisfaction in terminal Rajekwesi Bojonegoro and the result of F test simultaneous variable X1 (facility) and X2 (service quality) have significant influence to passenger satisfaction in terminal Rajekwesi Bojonegoro.